Effect of low-dose aspirin on reducing cardiovascular events and mortality in individuals with CKD stages 3–5: a meta-analysis of randomized controlled trials - Jingwen Lin; Xueqiong Cao; Wu Fu; Liu Yang; Wanxian Zeng; Na Li; Maobai Liu; Hongfu Cai (BMC Cardiovascular Disorders)
Abstract Background Chronic kidney disease (CKD) is a global health concern and an independent risk factor for cardiovascular disease. Despite optimal treatments, mortality remains high among CKD patients. This meta-analysis aimed to assess the balance between the cardiovascular benefits and the bleeding risks associated with the use of low-dose aspirin in patients with CKD stages 3–5. Methods Randomized controlled trials (RCTs) regarding the use of low-dose aspirin for cardiovascular primary prevention for patients with CKD were searched in PubMed, Embase, and the Cochrane Library. The Cochrane Collaboration RoB 2.0 tool was used to assess the risk of bias of RCTs. Major adverse cardiovascular events (MACE), including cardiovascular mortality, nonfatal myocardial infarction, and nonfatal stroke, along with other related outcomes, was calculated using a random-effects model to determine hazard ratios and relative risks (RRs). A subgroup analysis was stratified by estimated glomerular filtration rate (eGFR) levels to assess the differential effects of the treatment on patients with varying degrees of kidney function impairment. Results Five long-term RCTs were identified through systematic searches. Among them, 2 were at low risk, 2 had bias concerns, and 1 was at high risk. Aspirin significantly reduced the risk of MACE (RR, 0.76; 95% CI, 0.62–0.94), cardiovascular mortality (RR, 0.60; 95% CI, 0.43–0.85) and all-cause mortality (RR, 0.78; 95% CI, 0.63–0.96) in patients with CKD stages 3–5 compared to those not taking aspirin. When eGFR < 45 mL/min per 1.73 m2, the use of aspirin was associated with a significant reduction in the risk of myocardial infarction (RR, 0.47; 95% CI, 0.23–0.96) and cardiovascular mortality (RR, 0.47; 95% CI, 0.24–0.92). However, aspirin increased the risk of major bleeding in patients with CKD stages 3–5 compared to those not taking aspirin (RR, 1.50; 95% CI, 1.12, 2.02). Conclusions Low-dose aspirin provided significant benefits in preventing MACE, cardiovascular mortality and all-cause mortality in patients with CKD stages 3–5, particularly in preventing myocardial infarction, and cardiovascular mortality in those with an eGFR < 45 mL/min per 1.73 m2. However, the risk of major bleeding tended to increase as the eGFR decreased. For patient populations with a high risk of bleeding, it is necessary to re-evaluate the appropriateness of aspirin use.